Study of anti-inflammatory effect of a gel made from Minthostachys mollis (muña) in pawedema model, Arequipa - 2019. - Lily Jesús Mayorga Ruiz, (2019)
The investigation was developed, to verify the anti-inflammatory activity Minthostachys mollis (muña). And a gel was made from this medicinal plant. At the beginning of the investigation, the collection of Minthostachys mollis was carried out, for the taxonomic identification, then the plant was subjected to the processes of washing, drying, selection and grinding, to subsequently obtain the total essential oil, from which research was carried out by phytochemical analysis. When checking its effectiveness in the anti-inflammatory activity, the elaboration of a gel was formulated in order to use the essential oil of Minthostachys mollis (muña), as an active principle, afterwards the quality controls were carried out; in processes and in finished product. At the end of the investigation, the gel is presented in its effective formulation, which complies with quality parameters and good manufacturing practices and which can be used as a valid new therapeutic alternative for inflammatory problems. The species was collected from the department of Puno.